1-[x(1/5+1)-2/3]=x-75
1-6/5x+2/3=x-75
1+2/3+75=x+6/5x
230/3=11/5x
x=230/3:11/5=1150/33
1-[x(1/5+1)-2/3]=x-75
1-6/5x+2/3=x-75
1+2/3+75=x+6/5x
230/3=11/5x
x=230/3:11/5=1150/33
a)\(\left(1-\frac{1}{2}\right)x\left(1-\frac{1}{3}\right)x\left(1-\frac{1}{4}\right)x\left(1-\frac{1}{5}\right)x......x\left(1-\frac{1}{18}\right)x\left(1-\frac{1}{19}\right)x\left(1-\frac{1}{20}\right)\)
b)\(1\frac{1}{2}x1\frac{1}{3}x1\frac{1}{4}x1\frac{1}{5}x......x1\frac{1}{2005}x1\frac{1}{2006}x1\frac{1}{2007}\)
\(HELP\) \(ME\)\(!\)
1.
\(\frac{3}{4}x\frac{8}{5}:1\frac{1}{6}=\)\(2\frac{1}{3}x1\frac{1}{4}-\frac{7}{5}=\)\(4\frac{2}{3}+1\frac{1}{4}+2\frac{1}{3}+2\frac{3}{7}=\)2.
\(x.\frac{1}{2}=\frac{3}{4}+\frac{1}{5}\)\(x-\frac{1}{5}=\frac{2}{3}.\frac{9}{4}\)\(x.\frac{1}{5}+\frac{2}{3}=\frac{5}{4}\)\(\frac{13}{5}:x-\frac{1}{2}=\frac{4}{5}.\frac{15}{16}\)\(x:\frac{4}{9}+\frac{1}{3}=\frac{2}{5}.1\frac{13}{2}\)Chú ý: Dấu chấm là dấu nhân\(3\frac{2}{3}+2\frac{1}{5}x1\frac{4}{7}=?\)
\(3\frac{2}{3}-1\frac{1}{5}:2\frac{7}{9}=?\)
Chữ \(x\)\(\)trong câu đầu là dấu "x" (nhân)
Tìm \(x\):
a)\(x\) x \(3\frac{1}{3}=3\frac{1}{3}:4\frac{1}{4}\)
b)\(5\frac{2}{3}:x=3\frac{2}{3}-2\frac{1}{2}\)
c)\(\frac{x-1}{49}+\frac{x-2}{48}+\frac{x-3}{47}+\frac{x-4}{46}+\frac{x-5}{45}-5=0\)
Mình cần gấp !
2) Tim x
a)x + 4\(\frac{1}{5}\)= 5 \(\frac{2}{3}\)× 10\(\frac{1}{2}\)
b)\(\frac{24}{5}\)- x =2\(\frac{1}{4}\): 1\(\frac{3}{4}\)
Tính nhanh:
\(1\frac{2}{3}x1\frac{2}{5}x1\frac{2}{7}x.................x1\frac{2}{99}\)
1\(\frac{1}{2}\)x1\(\frac{1}{3}\)x1\(\frac{1}{4}\)x1\(\frac{1}{5}\)x1\(\frac{1}{6}\)x1\(\frac{1}{7}\)x1\(\frac{1}{7}\)x1\(\frac{1}{8}\)x 1\(\frac{1}{9}\)x 1\(\frac{1}{10}\)tính bằng cách thuận tiện nhất
tính giá trị biểu thức
\(\left(\frac{17}{10}+7-8,7\right):\left(\frac{23}{4}-\frac{11}{2}+\frac{9}{25}\right)x\left(12,98x0,25\right)+12,5\)
\(1\frac{2}{24}x5\frac{2}{5}x2x3\frac{7}{9}x2x\frac{2}{17}\)
\(2\frac{2}{17}x1\frac{1}{24}x5\frac{2}{5}x3\frac{7}{9}x2\)
\(3x\left(\frac{1}{7}+\frac{1}{3}-\frac{3}{14}\right):\frac{11}{14}\)
\(\left(1\frac{3}{2}+2\frac{1}{5}\right)x1\frac{1}{10}+\left(1\frac{7}{10}-\frac{4}{5}\right):\frac{3}{7}\)
Tim x
x*\(\frac{5}{2}\)-x*\(\frac{3}{4}\)=\(\frac{11}{56}\)
B) Tim phan so \(\frac{a}{b}\)
\(\frac{a}{b}\)*\(\frac{2}{5}\)+\(\frac{1}{5}\)*\(\frac{a}{b}\)=\(\frac{1}{12}\)+\(\frac{1}{4}\)